Bushmeat consumption among rural and urban children from Province Orientale, Democratic Republic of Congo - Vliet, N. van; Nebesse, C.; Nasi, Robert (Cambridge University Press, 2015)
Understanding the importance of bushmeat consumption for household nutrition, both in rural and urban settings, is critical to developing politically acceptable ways to reduce unsustainable exploitation. This study provides insights into bushmeat consumption patterns relative to the consumption of other meat (from the wild, such as fish and caterpillars, or from domestic sources, such as beef, chicken, pork, goat and mutton) among children from Province Orientale, Democratic Republic of Congo. Our results show that urban and rural households consume more meat from the wild than from domestic sources. Of the various types of wild meat, bushmeat and fish are the most frequently consumed by children from Kisangani and fish is the most frequently consumed in villages. Poorer urban households eat meat less frequently but consume bushmeat more frequently than wealthier households. In urban areas poorer households consume common bushmeat species more frequently and wealthier households eat meat from larger, threatened species more frequently. Urban children eat more bushmeat from larger species (duiker Cephalophus spp. and red river hog Potamochoerus porcus) than rural children (rodents, small monkeys), probably because rural households tend to consume the less marketable species or the smaller animals. We show that despite the tendency towards more urbanized population profiles and increased livelihood opportunities away from forest and farms, wildlife harvest remains a critical component of nutritional security and diversity in both rural and urban areas of the Democratic Republic of Congo.